Discovery Atlas of the world - Adelman, Elizabeth Fagan; Leverenz, Jon M. (Chicago : Rand McNally, 1993)
Features twenty-five pictorial maps showing terrain, animals, people, cities, and countries for each continent. Also includes illustrations of the characteristics of the regions.
Keywords: reference-atlases -- non-fiction